Velocity Components of Currents and Transport Mechanism in the Ie Meulee Waters, Weh Island, Indonesia - Ulung Jantama Wisha; Ilham Ilham (Jurnal Kelautan Tropis, 2019)
Weh Island has become an area of significance in which many developments are ongoing. Ie Meulee region was one of the developed areas where a new fishing port has been built which may impact to coastal instability. This study aims to determine the sea currents regime in the Ie Meulee waters and its relation to the transport mechanism. Field survey was conducted on March 2017 by which Tide Gauge and ADCP have installed within and without the port, respectively. Flow model was also simulated depicting current patterns for four extreme tidal conditions. The elliptical form of zonal and meridional components of current proves that the tidal current role takes place. The speed of tidal current ranged from 0-0.42 m/s and 0-0.85 m/s in the bottom and surface, respectively. The most prominent positive value of current components indicates that the transport mechanism is primarily surface ward during both ebb and flood tides. Reflection and diffraction are identified in the simulation testifying that the emergence of the fishing port has changed the hydrodynamic features. We also founded that the low-speed currents induced sediment settling within the jetty, so that it is essential to conduct regular dredging and bathymetry survey in the surrounding port.